Synthesis and characterization of γ-Fe2O3@SiO2–(CH2)3–PDTC–Pd magnetic nanoparticles: a new and highly active catalyst for the Heck/Sonogashira coupling reactions. (22nd May 2019) - Tashrifi, Zahra; Bahadorikhalili, Saeed; Lijan, Hossein; Ansari, Samira; Hamedifar, Haleh; Mahdavi, Mohammad
Abstract : A novel catalyst is synthesized based on the immobilization of palladium on γ-Fe2 O3 @SiO2 –(CH2 )3 –PDTC nanoparticles and is used as a highly active catalyst for the Heck/Sonogashira coupling reactions. Abstract : In this research, the synthesis and characterization of a novel catalyst is reported based on the preparation of the Pd complex of (pyridin-2-ylmethyl)dithiocarbamate (PDTC) supported on γ-Fe2 O3 @SiO2 magnetic nanoparticles (γ-Fe2 O3 @SiO2 –(CH2 )3 –PDTC–Pd). The catalyst is characterized by scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, thermogravimetric analysis, Fourier transform infrared spectroscopy, inductively coupled plasma analysis, X-ray powder diffraction, X-ray photoelectron spectroscopy, and vibrating-sample magnetometer measurements. The catalytic performance of γ-Fe2 O3 @SiO2 –(CH2 )3 –PDTC–Pd was evaluated in the Heck/Sonogashira coupling reactions of various aryl halides with various alkenes/phenylacetylene in water. The synthesized nanocatalyst showed a high catalytic activity even in very small amounts (5 mg, less than 0.1 mol%), was easily separated using magnetic decantation and was reused for ten cycles without any appreciable loss of its reactivity.